Optical Intelligent Reflecting Surfaces - Ajam, Hedieh; Schober, Robert (Intelligent Surfaces Empowered 6G Wireless Network, 2023)
Optical intelligent reflecting surfaces (IRSs) are planar structures which can manipulate the properties of an incident light wave, such as its polarization, phase, and amplitude in reflection and transmission. In this chapter, we investigate the modeling and design of IRS-assisted optical communication systems which can circumvent the line-of-sight (LOS) requirement in free space optical (FSO) systems. Unlike radio frequency (RF) systems, where the wavefront incident on the IRS can be modeled as planar and the power is uniformly distributed across the IRS, FSO systems employ Gaussian laser beams, which have a curved wavefront and a non-uniform power distribution. Therefore, a careful study of IRS-assisted FSO systems is needed as existing results from IRS-assisted RF systems are not applicable. This chapter studies the physical channel models for IRSs using scattering theory and geometric optics. We investigate the intermediate- and far-field regimes where the scattering theory can lead to an analytically tractable channel model for IRSs of different size and linear and quadratic phase-shift profiles. Using the geometric optics approximation, another simpler channel model neglecting the diffraction effect can be established for very large IRSs and specific phase-shift profiles. To employ the IRS for multiple FSO links and efficiently deploy large IRSs, sharing protocols, namely time division (TD), IRS division (IRSD), and IRS homogenization (IRSH) protocols are studied. Through simulations, we show that the IRSH protocol is preferable in the presence of misalignment errors. However, in the absence of such errors, the IRSD protocol is advantageous as it yields a higher received power than the IRSH protocol and a lower delay compared to the TD protocol.
CRIS-Team Scopus Importer:2024-12-16
Keywords: optical IRS; scattering theory; geometric optics